Voidable and void construction contracts - Yow, Kah Lun (2006)
Like other ordinary contracts, construction contracts are created when two parties, either between employers and contractors, contractor and supplier, or other combinations, mutually agree to a transaction. A contract may outwardly appear to satisfy all the requirements of a valid contract, but on closer examination the minds of the contracting parties are poles apart in respect of the terms of the contract. Such lack of genuineness may lead a construction contract to become void or voidable. According to Sweet (2000), it is difficult to determine the validity and voidability of a contract in the construction industry. There are circumstances which can cause a construction contract to become void or voidable, and those circumstances may not be easy to be determined. Hence, this dissertation intends to identify on what circumstances a construction contract will be rendered void or voidable. This dissertation was carried out mainly through documentary analysis of law journals. Meanwhile, due to time constraint, questionnaire survey and interviews were not carried out. There are six (6) circumstances have been identified which may render a construction contract voidable; and at the same time, another six (6) circumstances have been identified which may render a construction contract void. This dissertation perhaps is not comprehensive, it is, however, hoped that it may provides some rough ideas or guidelines for the parties in the construction industry when determining whether or not a construction contract is void, or voidable.